Establishing changes in the parameters of teat rubber for milking machines during testing and under industrial conditions - Paliy, Andriy; Aliiev, Elchyn; Paliy, Anatoliy; Ishchenko, Katerina; Rybalko, Ivan; Pavlichenko, Olena; Prihodko, Mikola; Popsui, Vjacheslav; Bondarchuk, Larisa; Chernyavskaya, Tetyana (Eastern-European Journal of Enterprise Technologies, 2023)
The teat rubber of milking machines is the only structural component of all milking and dairy equipment that is in contact with animals. During operation, the rubber article’s original quality characteristics are compromised. This is due to mechanical wear during operation. The task of the research is to establish changes in the parameters of the teat rubber of milking machines during testing and under industrial conditions. The object of research was the teat rubber of milking machines from various manufacturers, made of various composite materials. A scientific hypothesis put forward assumed that an increase in the efficiency of milking and dairy equipment could be achieved by establishing changes in the parameters of the teat rubber with subsequent maintenance planning. This would provide an opportunity to identify patterns and dependences that characterize these processes. In the course of research, theoretical dependences were derived to determine the operation of teat rubber in idle mode and the theoretical time of its operation. It was established that the theoretical wear period of the teat rubber is about 120–170 hours. It was determined that in the environment of SZHR-3, the coefficient of aging in terms of intensity was >2 times higher compared to Skydrol LD-4. The volume under similar conditions of exposure of liquids on samples exceeded by more than 3 times. It is proved that the change in the mass of rubber under the influence of SZHR-3 exceeds more than 2.5 times the indicators obtained from the effects of Skydrol LD-4. It was established that during long-term operation the teat rubber undergoes changes in its physical and mechanical properties. Thus, hardness and elasticity increase, elasticity decreases due to the destruction of the internal structure of rubber due to the formation of microcracks, the vacuum of closing the walls increases. Knowledge of the quality characteristics of the teat rubber would make it possible to find the optimal solution for the choice of rubber articles